Can I reach it? A study in age-related macular degeneration and glaucoma patients. Issue 9 (26th November 2019) - Lenoble, Quentin; Corveleyn, Xavier; Tran, Thi Ha Chau; Rouland, Jean-François; Boucart, Muriel
ABSTRACT: Aims : The visual exploration and the ability to correctly locate a target in reaching an object are critical in daily life. We investigate the object reachability judgment in neovascular age-related macular disease (nAMD) and primary open-angle glaucoma patients (POAG). Methods : Sixty-three participants were recruited in 4 groups (15 nAMD, 15 POAG, 18 old controls and 15 young controls). For each trial a cylinder moved between 11 random distances (from the border of their own peripersonal space 0, ±3, ±6, ±, ±12, ±15 cm). Participants had to estimate if they thought that the object was reachable or not. Results : POAG patients estimated that they could reach targets that were farther than their own peripersonal space (increased by 5.8 cm compared to the three other groups: 2.6 cm). The performance of the nAMD group and the normally sighted group were equivalent. Conclusions : The present study highlights the hypothesis of reach and grasps impairments in POAG due to difficulties in the estimation of reachability which is the beginning of any motor action processing. The reachability judgment of the nAMD patients is not affected. We conclude that POAG can modify the perceived peripersonal space of the patients and induce changes in the reachability judgment.